Symphony no. 2 manuscript parts - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (2023)
Incomplete set of manuscript parts for Beethoven's Second Symphony in D major, op. 36, arranged for small ensemble (strings, 2 clarinets, 2 flutes), written in several unidentified hands on music paper with hand-drawn staff lines, undated (possibly from the late 19th century).